Effect of Exogenous Organic Acids Application on Cr Uptake by Leersia hexandra Swartz - Cai, X.W.; Zhang, X.H.; Zhang, H. (Asian Journal of Chemistry, 2010)
A study was conducted to three different Leersia hexandra Swartz populations to test the effect on Cr mobilization, Cr accumulation and the growth situation of EDTA, citric acid, oxalic acid and malic acid. The results showed that EDTA had significant effect on mobilization of Cr in soil, exchangeable Cr in soil increased 80.3 % contrasting control, citric acid, oxalic acid and malic acid had passivation effect on the Cr in soil. Organic acids increased the growth rate contrasting control and citric acid increased it fastest which is 4.11 mm/day; EDTA promoted the Cr uptake significantly. The Cr content in the roots was 3 times higher than that of control. The migration coefficient increased by 24 % compared to control, citric acids had no influence on mobilization of Cr and accumulation, however, oxalic acid and malic acid retrained the mobilization of Cr, decreased the accumulation of Leersia hexandra Swartz slightly.